Entre o risco criado e o risco-proveito: uma discussão acerca da cláusula geral de responsabilidade objetiva do parágrafo único do artigo 927 do Código Civil de 2002 - RODRIGUES, Arley Dieminger (2021)
The purpose of this study was to analyze, from a civil-constitutional perspective, the sub-theories of the risk theory, in order to identify which would best apply to the 2002 Civil Code in its general objective liability clause, contained in the sole section. For this goal, we use the analytical-critical method, through the reading of scientific articles, legal provisions, court decisions, doctrinal books and electronic journals. In this regard, we note the uncertainty, both regarding doctrine and case law, as to which sub-theory of risk would best apply to the general objective liability clause of the 2002 Civil Code. It was found that the controversy appeared to lie among the sub-theories of occupational risk, benefit risk and the risk created, the last two being considered the major target of divergences. Thus, we conclude that the risk-benefit sub-theory would be the most in line with the demands of the legal system, since we believe it to be the sub-theory that best reconciles the demands of the principle of solidarity with those of the principle of freedom.